Influence of personal value orientations on pro-environmental behaviour: a case of green shopping bags - Muposhi, Asphat; Wait, Marius; Mpinganjira, Mercy (Inderscience, 2022)
Limited success has been reported thus far on the effectiveness of government interventions such tax in promoting the use of green shopping bags in South Africa's grocery retail sector. This study represents an initial effort in an emerging market to understand the influence of value orientations in promoting the use of green shopping bags. This study employs the value-belief-norm theory to examine whether personal values influence the use of green shopping bags in South Africa. Self-reported data was collected from a convenient sample of 487 consumers using a questionnaire survey. Structural equation modelling results identified biospheric value as the major predictor of new ecological paradigm. The relationship between altruistic value and new ecological paradigm was found to be insignificant. Awareness of consequences was found to have a positive significant influence on ascription of responsibility. Furthermore, personal norm managed to explain a significant variance in the behaviour of using green shopping bags. The findings of this study support the use of personal value orientations in formulating policies aimed at promoting the use of green shopping bags.